Sistem Monitoring Kualitas Air pada Akuarium Budidaya Ternak Ikan Guppy Menggunakan Mikrokontroler Berbasis IoT - Nivika Tiffany; Nandhika Darwin; Dede Furqon Nurjaman; Muhammad Reza Hidayat; Naftalin Winanti (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2022)
Ornamental fish cultivation in Indonesia is growing rapidly, data from Ministry of Maritime Affairs and Fisheries (KKP) shows at least 4.720 species of fish, freshwater, and marine, 650 species are ornamental fish. KKP also noted that the production of ornamental fish increased, commodities increased significantly were Guppy (82.5%), Koki (61.7%), Corydoras (38.6%), Betta (16.4%) and Koi (8.9%). In order to produce quality fish, air quality such as pH, TDS, and temperature must be considered. Ornamental fish can survive conditions with pH value of 6.5-8.5, TDS value of 200 ppm and temperature below 28-32°C. The study designed an air quality monitoring system using a microcontroller based on IoT. The sensors used to measure water quality parameters are PH4502C, SEN0244, and DS18B20. The value read by the sensor will be collected and processed in microcontroller, microcontroller used in this system is Arduino Uno. The processed data will be sent to broker via NodeMCU using MQTT protocol. After data arrives at broker, data will be generated by two interfaces, interface is dashboard and augmented reality. The results of this system experiment present that data experiments it can be seen error rate of the pH sensor is 0.80, TDS 1.89, and temperature sensor 1.18.